2006
DOI: 10.2337/diacare.29.02.06.dc05-1781
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Intervention Is Associated With Lower Prevalence of Urinary Incontinence

Abstract: OBJECTIVE -Diabetes is associated with increased urinary incontinence risk. Weight loss improves incontinence, but exercise may worsen this condition. We examined whether an intensive lifestyle intervention or metformin therapy among overweight pre-diabetic women was associated with a lower prevalence of incontinence.RESEARCH DESIGN AND METHODS -We analyzed data from the Diabetes Prevention Program, a randomized controlled trial in 27 U.S. centers. Of the 1,957 women included in this analysis, 660 (34%) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
109
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 28 publications
4
109
0
8
Order By: Relevance
“…Of note, rates of incontinence were seen to be as high as 38%. 18 Women with a history of GDM tend to be poor and racial/ethnic minorities and also have low education levels and incomes, as opposed to our largely non-Hispanic white, well-educated, and affluent sample. It is possible that less advantaged women are more affected by stress urinary incontinence than our sample, perhaps because they have low self-efficacy for physical activity already, and stress incontinence is more difficult to surmount.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Of note, rates of incontinence were seen to be as high as 38%. 18 Women with a history of GDM tend to be poor and racial/ethnic minorities and also have low education levels and incomes, as opposed to our largely non-Hispanic white, well-educated, and affluent sample. It is possible that less advantaged women are more affected by stress urinary incontinence than our sample, perhaps because they have low self-efficacy for physical activity already, and stress incontinence is more difficult to surmount.…”
Section: Discussionmentioning
confidence: 74%
“…17,18 In NHANES, the frequency of stress incontinence was assessed by the question: "During the past 12 months, have you leaked or lost control of even a small amount of urine with an activity like coughing, lifting, or physical activity?" We modified this question by replacing "during the past 12 months" with "during your [GDM] pregnancy" and also "after your [GDM] pregnancy."…”
Section: Stress Urinary Incontinence Measuresmentioning
confidence: 99%
“…However, autonomic neuropathy affecting the innervations of the striated muscle of the urethral sphincter and pelvic floor muscles can lead to the development of an incompetent urethral mechanism and consequently stress UI [11]. Obesity, which is often associated with type 2 DM, is also a well-known risk factor for development of stress UI due to increased intra-abdominal and pelvic pressure [12]. Causes of stress UI in diabetic women also include the effects of gestational diabetes and delivery conditions such as macrosomia, prolonged second stage of labor, and the increased risk of instrumental delivery on the pelvic floor.…”
mentioning
confidence: 99%
“…Weight loss, in obese patients, through diet and exercise, has long been advocated as an integral part of the conservative management plan for women with UI. Interestingly, a number of studies have also shown that the development of DM can be prevented by lifestyle interventions like exercise and diet regulation with a consequent decrease in the overall prevalence of female UI by nearly 50 % [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation